PENERAPAN PENILAIAN DALAM KURIKULUM 2013 PADA TINGKAT DASAR MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Isnawati Nur Afifah Latif; Nurlaili Dina Hafni (PREMIERE : Journal of Islamic Elementary Education, 2019)
In the 2013 curriculum, the concept of assessment to understand learning through competence refers to three approaches, namely assessment as learning, assessment for learning, assessment of learning. All three approaches must be taken by the teacher in the assessment activities. assessment as learning is carried out during the learning process by expecting results in the form of information to the teacher about students' readiness to understand deeper concepts. Assessment for learning. Assessment of learning is carried out by the teacher to measure the level of achievement of student competencies that can be known from previous learning assessments. In Islamic education subjects, the competencies assessed cover three aspects, namely aspects of knowledge, attitudes, and skills. Thus, the valuation technique must be adjusted so that the assessment and the results obtained are appropriate so that all interested parties can optimally utilize the results of the assessment.